Impact of Whole Genome Sequencing to investigate transmission of Serratia marcescens in Neonatal Intensive Care Unit - Cristina Merla; Marina Ramus; Angela Kuka; Irene Mileto; Stefano Gaiarsa; Amelia Di Comite; Marta Corbella; Antonio Piralla; Marina Liliana Lanave; Alba Muzzi; Stefano Ghirardello; Fausto Baldanti; et al. (Elsevier, 2024)
Newborns admitted to neonatal intensive care units (NICU) are at increased risk of health care-associated infections. Serratia marcescens represent the third most common pathogen in NICU outbreaks. Here we present an outbreak investigation performed using Whole Genome Sequencing (WGS) analyses and the control measures implemented to limit the spread of S. marcescens in the NICU of an Italian hospital. In February 2023 S. marcescens was isolated from six newborns, when in 2022 this pathogen was isolated only from two samples in the same ward. Measures for infection prevention were adopted. Routinary surveillance screening, performed with rectal swabs collected at admission and weekly thereafter, was implemented to search for S. marcescens presence. Environmental samples were collected. All the isolates, obtained from the conjunctival swab of six newborns, from rectal swab of two newborns who did not develop infections, as well as from the aerators of two faucets, were sequenced. WGS analyses showed no correlation between the isolates from newborns and environmental isolates. The implementation of the measures for infection prevention and control had enabled us to successfully control the outbreak within a short period. WGS analyses proved to be crucial in outbreak investigation to limit the spreading of the pathogens.